Factors Influencing Auditors' Acceptance Of The Practice Review System - Ismail, Sarina (2006)

(untitled)
This research was carried out to identify the factors that influence auditors' acceptance of the Practice Review System. Using a theoretical model based on the Decomposed Theory of Plmmed Behavior, this study aims to identify the factors influencing acceptance of the Practice Review System. This research serves to test the applicability of the Decomposed TPB in predicting auditors' behavioral intention to accept the Practice Review System. Questionnaire Survey was used in this research. Kajian ini dibuat untuk mengaJI kecenderungan sikap tingkap laku juruaudit untuk menerima Sistem Penyemakan Amalan. Kajian ll11 Juga bertujuan untuk mengklasifikasikan fakta - fakta yang mempengaruhi tingkahlaku juruaudit untuk menerima Sistem Penyemakan Amalan. Model yangdigunakan ialah "Decomposed Theory of Planned Behavior" (DTPB). Di samping itu juga, kajian ini ingin mengkaji kesesuaian model "DTPB" di dalam meramalkan tingkahlaku juruaudit untuk menerima Sistem Penyemakan Amalan.